HUBUNGAN KEPATUHAN MINUM OBAT HIPOGLIKEMIA ORAL DENGAN KADAR GULA DARAH DAN KUALITAS HIDUP PADA PASIEN DIABETES MELLITUS TIPE II DI RSUD MEURAXA BANDA ACEH - Sri Marlinda; Zurriyani Zurriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Diabetes mellitus type 2 (type 2 DM) is a chronic metabolic disease that is one of the world's health problems with an ever-increasing prevalence. Controlling in adequate therapy reduces the quality of life of type 2 DM. The quality of life of DM tie 2 may be influenced by adherence to oral hypoglycemic (OHO) medications and blood sugar levels. The purpose of this study was to determine adherence to taking oral hypoglycemic drugs with blood sugar levels and quality of life in patients with type 2 diabetes in Meuraxa Hospital Banda Aceh City. This study using analytic study with retrospektif design. The sample size was 53 people who gathered accedential sampling, quality of life was assessed using the SF-36 questionnaire, adherence OHO was assessed using the MMAS-8questionnaire. Blood sugar levels obtained from laboratory results or recording blood sugar levels of patients. The conclusion of this study is that there is a highly significant relationship between adherence OHO with blood sugar levels in patients with type 2 diabetes with a value of p = 0.00, and there is no relationship between adherence OHO with the quality of life of patients with type 2 diabetes with a value P = 0.34.Keywords: Compliance, Type 2 diabetes,Blood Sugar Level, Quality of Life